Common inputs in subthreshold membrane potential: the role of quiescent states in neuronal activity - Montangie, Lisandro (2018)
Experiments in certain regions of the cerebral cortex suggest that the spiking activity of neuronalpopulations is regulated by common non-Gaussian inputs across neurons. We model these deviations from random walk processes with q-Gaussian distributions into simple threshold neurons, and investigate the scaling properties in large neural populations. We show that deviations from the Gaussian statistics provide a natural framework to regulate population statistics such as sparsity, entropy and specific heat. This type of description allows us to provide an adequate strategy to explain the information encoding in the case of low neuronal activity and its possible implications on information transmission.